Pengaruh Konservatisme Akuntansi Dan Debt Maturity Terhadap Efisiensi Investasi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2021 (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the effect of the effect of accounting conservatism and debt maturity on investment efficiency in manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. The research sample used was 20 companies, where the method in sampling this study used purposive sampling method sampling with predetermined criteria. The analysis method used is Multiple Linear Regression Analysis. This test was carried out using the SPSS 16.0 for windows program. Simultaneous test results show that accounting conservatism and debt maturity affect investment efficiency. Partial test results show that accounting conservatism has a negative effect on investment efficiency. While debt maturity has a positive effect on investment efficiency.